Impactos antrópicos na qualidade da água na Bacia Hidrográfica do Rio São Francisco Verdadeiro - Schmidt, Adir Otto (2014)
The western Paraná region has experienced an economic moment in which, in rural areas, there is some need to intensify livestock production. In cities, the process of urbanization is reinforced, with possible impacts on water resources, mainly sediments load and the process of rivers eutrophication. In order to contribute to the sustainable development of the region, the present study aimed at evaluating the anthropic impacts on water quality in the Basin of São Francisco Verdadeiro River. Thus, from July 2011 to June 2013, 52 monitoring campaigns have been carried out in every two weeks. Water samples were collected in nine (9) strategic locations of the watershed and a local control. The sites collections were defined considering the possibility of distinguishing the impacts of each activity developed along the watershed. Water samples were collected in 9 strategic locations throughout the watershed and a control area. The areas were defined according to the possibility of differentiating the impacts on each activity developed along the basin: a) flow measurements, dissolved oxygen, pH, conductivity, temperature, turbidity and analyses of concentrations of chlorophyll-a, orthophosphate, total phosphorus, organic carbon and total nitrogen; b) estimated yield and load suspension sediments using as reference Tomazoni et al. (2005) and Guimarães (2010) studies; c) unconformities identification to classify the rivers in Class II according to Resolution 357/05 – CONAMA; and e) Trophic state index - TSI evaluation. The results showed that the estimated sediment discharges were 171,093 and 230,281 t year-1, respectively in accordance with the references used, with low discharges in the headwater sub-basins and moderate and high discharges for the intermediate and final sub-basins. Unconformities were identified to classify in Class II for turbidity and phosphorus for the 9 surveyed areas. The trophic degree was considered mesotrophic in 6 areas; eutrophic, supereutrophic and hypereutrophic, in an area for each classification. At last, it can be concluded that few high discharge events have most contributed with the sediment discharge, that total phosphorus concentration is over the desirable originating values from urban activities, this is the greatest impact on water quality and that turbidity and electrical conductivity are useful parameters to predict phosphorus in hydric environments